K-AR AGE OF VOLCANISM IN SOUTH KAMCHATKA - Sheimovich V.S.; Karpenko M.I. (My University, 1996)
For the purpose of the geological mapping of Cenozoic volcanic rocks in South Kamchatka, K-Ar ages of the rocks were determined using 30 whole rock samples. The rocks of the andesite association were found to be of the oldest (Miocene) age 14-16 Ma. The subvolcanic dacite bodies and granodiorite intrusions, attributed to this rock association, were dated 9.6-11.7 Ma. The ages of the Pliocene rocks of the andesite-basalt association range between 2 and 5 Ma. The Neogene rocks of the rhyodacite association (rhyolites and ignimbrites) have K-Ar ages between 0.5 and 1.4 Ma. The various facies of one rock complex yielded similar absolute age values.
Keywords: Cenozoic; Neogene; Pliocene; Miocene; Cenozoic; Кайнозой::Неоген; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Pliocene; Кайнозой; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Cenozoic::Neogene